Evidências formativas da extensão universitária na docência em Educação Física - Nozaki, Joice Mayumi; Ferreira, Lílian Aparecida [UNESP]; Hunger, Dagmar Aparecida Cynthia França [UNESP] (Universidade Federal de São Carlos, 2015)
In the initial training of graduate courses in Physical Education, especially in public institutions, the university extension has been shown to be an increasing and diversified space of projects and activities that every day include a larger number of graduates as fellows and/or volunteers. In such projects, concrete experiences of action are highlighted, which are organized and supervised by a coordinator teacher, and they may be materialized as a fertile space for teacher training. Therefore, this study aimed to examine the implications of a university extension project in the initial training of the teachers and in the role of physical education teacher. The methodology was based on a qualitative exploratory research that used the questionnaire as a collection technique. Six PE teachers participated in the study, and, when they were students graduate, they attended the same university extension project. The main reflections brought by the survey were found in three types of analysis, namely: Approach, organization and construction of pedagogical practice; Group work in training; Articulation between initial training and professional performance. In general, the survey identified the university extension as an essential and enriching process of initial training for teachers and professional practice in teaching Physical Education.

Na formação inicial dos cursos de licenciatura em Educação Física, especialmente nas instituições públicas, a extensão universitária tem se evidenciado como um espaço crescente e diversificado de projetos e atividades que vem a cada dia incluindo um número maior de graduandos como bolsistas e/ou voluntários. Em tais projetos são evidenciadas experiências concretas de ação que são organizadas e orientadas por um professor coordenador, podendo se materializar como espaço fértil para a formação docente. Sendo assim, essa pesquisa teve como objetivo analisar as implicações de um projeto de extensão universitária na formação inicial do licenciado e na atuação do professor de Educação Física. A metodologia se pautou por uma pesquisa qualitativa de caráter exploratório que utilizou o questionário como técnica de coleta. Os participantes do estudo foram seis professores de Educação Física que, quando alunos da graduação, participaram de um mesmo projeto de extensão universitária. As principais reflexões trazidas pela pesquisa foram evidenciadas em três categorias de análise, a saber: Aproximação, organização e construção da prática pedagógica; O trabalho em grupo na formação; Articulação entre formação inicial e atuação profissional. Em linhas gerais, a pesquisa identificou a extensão universitária como um processo essencial e enriquecedor da formação inicial dos licenciados e da atuação profissional docente em Educação Física.
Formative evidences of university extension in Physical Education teaching
Keywords: University extension; Teacher training; Physical education; Degree; Extensão universitária; Formação docente; Educação física; Licenciatura